1970
DOI: 10.2514/3.29966
|View full text |Cite
|
Sign up to set email alerts
|

Langmuir probe measurements in a discharge from a hollow cathode

Abstract: U SE of the vapor-fed hollow cathode both as plasma-bridge neutralizer and as the ion chamber electron source has been advantageous in mercury bombardment ion thrusters. 1^3 A hollow cathode differs from earlier types (e.g., refractory metal ribbon, or oxide magazine) in several important ways. For example, it is-a source of mercury atoms, as well as of electrons. Consequently, a very large pressure gradient exists just outside the hollow-cathode orifice as a result of the mercury vapor expanding into a region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

1975
1975
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 2 publications
1
18
0
Order By: Relevance
“…This significant perturbation strongly suggests that probe insertion and measurement were associated with a change of the cathode regime from the spot to the plume mode. This would explain the higher electron temperatures measured with the probe, on the order of those expected in a plume mode [2]. Nevertheless, plume modes are usually associated with lower electron density.…”
Section: Comparison With Its Measurementsmentioning
confidence: 78%
See 1 more Smart Citation
“…This significant perturbation strongly suggests that probe insertion and measurement were associated with a change of the cathode regime from the spot to the plume mode. This would explain the higher electron temperatures measured with the probe, on the order of those expected in a plume mode [2]. Nevertheless, plume modes are usually associated with lower electron density.…”
Section: Comparison With Its Measurementsmentioning
confidence: 78%
“…The spot mode is usually the operation mode desired and is associated with high electron density, low electron temperature (Csiky identified this mode with temperatures in the range of 0.5 eV [2]) and low discharge oscillation. The plume mode is associated with lower electron density, higher electron temperature (in the range of 1 -2 eV in reference [2]) and higher oscillations of the discharge voltage and current (a ratio I d,std /I d,mean above few percent is usually attributed to the plume mode [32]), leading to a lower cathode lifetime [33]. The experimental work presented in this article focuses on discharge conditions for which the cathode discharge is in the so-called spot mode.…”
Section: Cathode Details and Operationmentioning
confidence: 99%
“…Cathode discharge modes and mode transition are described by several theories 8,9,30 . One of them suggests that when the passive current to the anode, i.e.…”
Section: B Discharge Modesmentioning
confidence: 99%
“…1 This erosion is typically associated with large-scale oscillations in plasma potential that onset in the so-called plume mode. 2 By including these oscillations empirically into numerical models, it is possible to recover measured erosion rates. 3 Hollow cathodes for electric propulsion have been in development for decades and these studies have identied empirical techniques for avoiding the plume mode -namely increasing the ow rate through the cathode.…”
mentioning
confidence: 99%
“…For example, the rst series of measurements of the instabilities associated with plume mode indicated that they onset at high current or low propellant ow rate. 2,6,7 Historically, this onset criterion is commonly interpreted as an indication that the plume mode is the result of an ionization type instability. It has been theorized to follow a predator-prey model where the ionization rate rises at suciently high current (or low ow rate) leading to a depleted neutral population.…”
mentioning
confidence: 99%